Using Nematodes to Control Insects: Overview and Frequently Asked Questions - William T. Crow (EDIS)
This document is ENY-050, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: December 2002.